2014
DOI: 10.1021/jp509683g
|View full text |Cite
|
Sign up to set email alerts
|

Helium Nanodroplet Study of the Hydrogen-Bonded OH Vibrations in HCl–H2O Clusters

Abstract: Mixed (HCl)N(H2O)M clusters have been assembled in He droplets from the constituting molecules. Spectra of the clusters were obtained in the range of hydrogen-bonded OH vibrations (3100-3700 cm(-1)) by infrared laser depletion spectroscopy. The observed bands were assigned to cyclic hydrogen-bonded aggregates containing up to two HCl and three H2O molecules. The obtained frequencies are in good agreement with the results of harmonic quantum chemical calculations upon appropriate uniform shifts mimicking anharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…The binding preference of water molecules to imidazole has been investigated by supersonic jet FTIR with O 18 substitution and it was found that the water molecules prefer to act as hydrogenbond donors (O-HÁ Á ÁN). 15 Nuclear magnetic resonance (NMR) has been extensively used to elucidate the structural properties of imidazole and imidazole containing molecules as well as the proton transfer mechanism. [16][17][18][19][20][21] However, the signal from the two pseudoequivalent nitrogen atoms in imidazole is not distinguishable by 15 N NMR [16][17][18] due to the low time resolution (10 À5 seconds) of NMR, which cannot capture the rapid tautomeric exchange between the nitrogen moieties (picoseconds).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding preference of water molecules to imidazole has been investigated by supersonic jet FTIR with O 18 substitution and it was found that the water molecules prefer to act as hydrogenbond donors (O-HÁ Á ÁN). 15 Nuclear magnetic resonance (NMR) has been extensively used to elucidate the structural properties of imidazole and imidazole containing molecules as well as the proton transfer mechanism. [16][17][18][19][20][21] However, the signal from the two pseudoequivalent nitrogen atoms in imidazole is not distinguishable by 15 N NMR [16][17][18] due to the low time resolution (10 À5 seconds) of NMR, which cannot capture the rapid tautomeric exchange between the nitrogen moieties (picoseconds).…”
Section: Introductionmentioning
confidence: 99%
“…15 Nuclear magnetic resonance (NMR) has been extensively used to elucidate the structural properties of imidazole and imidazole containing molecules as well as the proton transfer mechanism. [16][17][18][19][20][21] However, the signal from the two pseudoequivalent nitrogen atoms in imidazole is not distinguishable by 15 N NMR [16][17][18] due to the low time resolution (10 À5 seconds) of NMR, which cannot capture the rapid tautomeric exchange between the nitrogen moieties (picoseconds). X-ray spectroscopic techniques have also been utilised to examine the local environment around imidazole in aqueous solutions and to probe the changes induced by phase transition, 22,23 solvation, [22][23][24] and protonation.…”
Section: Introductionmentioning
confidence: 99%
“…The literature related to the dissociation of acids in aqueous environments and the microsolvation of the resulting anions and protons is extensive . In 2011, Leopold published a comprehensive review of this topic, in which Table 1 collects experimental and theoretical evidence about the number of water molecules needed to dissociate some simple acids, suggesting four water molecules for the case of HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Few experimental studies are reported on the vibrational spectroscopy of small HCl–(H 2 O) n clusters in a molecular beam due to difficulties encountered in assigning their infrared (IR) spectra. Specifically, when a mixture of HCl and H 2 O is expanded, (HCl) m –(H 2 O) n clusters with several m and n combinations are formed, and probing selected clusters depends on the ability to assign their spectra. The spectra contain broad peaks from larger clusters overlaid with sharper peaks from smaller clusters with m = 0–4 and n = 1–4. , The theoretical studies of Mancini and Bowman identified spectroscopic features in the regions of the OH and HCl stretch vibrations, but within the accuracy of the theoretical treatment, it was difficult to assign conclusively features belonging to specific clusters .…”
mentioning
confidence: 99%
“…The spectra contain broad peaks from larger clusters overlaid with sharper peaks from smaller clusters with m = 0–4 and n = 1–4. , The theoretical studies of Mancini and Bowman identified spectroscopic features in the regions of the OH and HCl stretch vibrations, but within the accuracy of the theoretical treatment, it was difficult to assign conclusively features belonging to specific clusters . Fortunately, Zischang et al have recently reported experimental assignments of the H-bonded OH stretch fundamentals at 3100–3700 cm –1 , which have made the vibrational predissociation (VP) study reported here feasible.…”
mentioning
confidence: 99%